“MY STRUGGLE” – FROM AUTOBIOGRAPHY TO PERFORMATIVE BIOGRAPHISM - POPA, Ștefana (Studia Universitatis Babeș-Bolyai Philologia, 2017)
My Struggle – from Autobiography to Performative Biographism. The present article aims at showing that the work of the contemporary Norwegian author Karl Ove Knausgård, a series of six volumes entitled My Struggle, fulfills the criteria specific to various literary (sub)-genres. I will investigate the particularities that raise the most questions regarding the framing of such a work and analyze three categorizations of My Struggle, i.e. autobiography, autofiction and performative biographism. The analysis will be constructed especially in the context of Norwegian and Scandinavian literary space, but international perspectives will also be taken into consideration. REZUMAT. Lupta Mea – de la autobiografie la biografism performativ. Articolul de față își propune să arate că proza în șase volume Lupta Mea, a autorului norvegian contemporan Karl Ove Knausgård, îndeplinește criteriile de analiză specifice mai multor (sub)-genuri literare. Se vor investiga particularitățile care problematizeaza localizarea operei intr un gen proxim și se vor examina trei posibile încadrări ale acesteia, ca autobiografie, autoficțiune și biografism performativ. Analiza va fi construită în special în contextul spațiului literar norvegian și scandinav, dar vor fi luate în considerare și perspective internaționale, atunci când va fi cazul. Cuvinte cheie: autobiografie, autoficțiune, literatură norvegiană, pact ficțional, adevăr